A review on breast cancer in Iraq and future therapies insights - Nawfal N. Alrawi (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Cancer is one of the most common diseases around the world and the second leading cause of death after cardiovascular disease. Breast cancer is the most prevalent cancer type among Iraqi women, as it represents the highest percentage of malignant tumors in women until 2018. Therefore, women should be aware of the aggravation of this disease, the importance of the periodic examination for early detection for breast cancer, and following the most appropriate means for the treatment to get recovered and, thus, to reduce mortality. To fight cancer, there is an urgent need to search for new effective anticancer therapies that alter the molecular biology of tumor cells, stimulate the immune system, or specifically deliver chemotherapy factors directly to cancer cells without affecting normal cells and reducing the side effects of treatments. In this context, this paper aimed to highlight the therapeutic approaches used in the current researches of breast cancer treatment. Accumulated evidence showed that medicinal plants extracts, virotherapies, and nanomaterials can serve as anticancer agents. The proposed mechanisms were discussed and presented in this review.